Study of intravitreal injection of bevacizumab or lucentis before Ahmed glaucoma valve implantation on the treatment of neovascular glaucoma - Yong Liu (Guoji Yanke Zazhi, 2015)
AIM:To evaluate the efficacy and safety of Ahmed glaucoma valve implantation(AGVI)combined with different anti-vascular endothelial growth factor(VEGF)agent injected before surgeries for neovascular glaucoma(NVG). METHODS:This was a retrospective case controlled study on patients with NVG in whom AGVI was performed between September 2009 and November 2013. The sample was divided into two groups according to the pretreatment:the intravitreal injection of bevacizumab or lucentis. The success rate of surgeries, intraocular pressure(IOP), the number of antiglaucoma medications used after surgeries, best correct visual acuity(BCVA), postoperative complications, regression and recurrence of iris neovascularization were analyzed between the groups. RESULTS:Compared with preoperative, IOP, the number of antiglaucoma medications used of the two groups decreased significantly at every follow-up(P<0.05). There were no significant difference on postoperative IOP, the number of postoperative antiglaucoma medications, and BCVA between bevacizumab and lucentis groups. Kaplan-Meier survival curves showed that the success rate was 80.6% for the bevacizumab group and 79.3% for the lucentis group at endpoint of follow-up, the difference between the two groups was not significant(P=0.896). There was no significant difference on the complete success rates between the two groups(P=0.753). CONCLUSION:Preoperative intravitreal injection of bevacizumab/ lucentis may be an effective and safe combined with AGVI on managing NVG. However, the two drugs have the similar efficacy and safety.